A study on the effect of protein levels andbalance lysine/methioned in layer diets withand without fish meal' - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Two hundred and fourty-22 week old pullets were randomly alloted to 12 iso-caloric (2,700 kcal/kg) dietary treatments to meansure the biological effect and income over feed cost (IOFC) of formulation diets consisting of three protein levels (15, 16 and 17%), two combination levels of lysine/methionine (0.80 %/0.40% and 0.85 %/0.43 %) and two type of diets (fish meal and all grain diets). Each dietary treatment was replicated to 5 with 4 pullets each. The other 5x4 pullets were also included and fed with commercial diet. The biological assay was factorially arranged in 3 x 2 x 2 and replicated to 5 for 6x28 days period of egg production. All parameters concerned with egg production were measured. Feed intake and egg production (HDA/HHA) statistically (P... Key word: Protein level, Lysine, Methionine, Fish meal, Performance, Layer